Collaborative Approach to Developing Infection Prevention Control Recommendations at a Tertiary-Care Pediatric Hospital. (October 2020) - Lee, Bonita; Durand, Joan; Jones, Helen; Gartner, Nicole; Driscoll, Jennifer; Watson, Cheryl; Chandran, Uma; Sivarajan, Veena; Pereira, Nichole; Clonfero, Maria; Degroot, Jaylene; Childs, Michelle
Abstract : Background: Stollery Children's Hospital (SCH) is a tertiary-care pediatric hospital with a complex infrastructure: 3 NICUs located at 3 different hospitals, and all of the pediatric inpatient beds, PICU, PCICU, and a medical-surgical NICU at the main SCH site shared buildings with an academic adult hospital. We describe a collaborative process used to develop standardized SCH Infection Prevention and Control (IPC) recommendations. Methods: The SCH IPC formed a working group with Patient and Family-Centered Care (PFCC) and family representatives in 2014 to enhance the engagement of families in regards to IPC issues and initiatives. The working group identified inconsistent messages provided to families when a child was admitted as a patient requiring additional precautions (PRAP). The working group then developed a framework of key questions to be answered for family care providers of PRAP. The working group held several consultative meetings with frontline staff followed by a review of published guidelines and consultations with other pediatric hospitals about contentious issues. A consensus meeting with all key stakeholders was held to finalize IPC recommendations. Results: The key contentious issues included (1) whether personal protective equipment is required for family care providers who stay overnight with PRAP and (2) whether family care providers of PRAP are allowed to access nutrition centers on clinical units and family lounges in PCICU–PICU–NICU that were stocked with free hot meals for the families. No directly applicable recommendation was available IPC guidelines on these issues. Discussions of these topics were directed by PFCC at family councils of various clinical programs with efforts to seek opinions from more family representatives. Expert opinions and current practice were also obtained from Canadian hospitals through emails and from US hospitals through SHEA Open Forum by ICP. A final consensus meeting revisiting all available information was held, and a new Stollery IPC guideline was created with families as partners sharing the IPC vision of minimizing transmission risk at SCH. Conclusions: A consultative engagement and consensus process was successful in the development of IPC recommendations for family care providers for PRAP for implementation at a tertiary-care pediatric hospital with a complex infrastructure. The next step is to develop family-friendly educational and resource materials with clear and concise messages. Funding: None Disclosures: None